Classement d’un sous-ensemble de phrasèmes en discours : les formules conversationnelles (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
Based on Spanish and French examples, this article presents the classification Classement d’un sous-ensemble de phrasèmes en discours : les formules conversationnelles of a subset of idioms in discourse, which in the Hispanic research on phraseology have been called fórmulas rutinarias (Corpas Pastor, 1996) or pragmatemas (Blanco, 2010). After having excluded from our analysis the forms whose use is limited to written texts, such as those used in correspondence (Sincerely; Amicalement), in academic writings (Emphasis added; C’est nous qui soulignons) or in traffic signs (road work; attention travaux), we reserve the name of « conversational formulae » for phraseological statements of talk-in-interaction. This new classification, based on pragmatic and discursive criteria and carried out in a contrasting and translating Spanish- French / French-Spanish perspective, aims to help the translator, lexicographer and FLE or ELE teacher to solve decoding, encoding and reformulation problems.
Keywords: conversational formulae, French-Spanish, classification, pragmatic and discursive criteria